2014
DOI: 10.1080/21650373.2014.928808
|View full text |Cite
|
Sign up to set email alerts
|

Degree of hydration-based creep modeling of concrete with blended binders: from concept to real applications

Abstract: The mechanical behavior of hardening concrete is to a large extent determined by the evolving microstructure as a result of the hydration process. For traditional binder systems, consisting of Portland cement or blast furnace slag cement, the degree of hydration is known to be a fundamental parameter in this respect, enabling a detailed study and accurate prediction of the early-age mechanical behavior, including basic creep. Nowadays, in view of improved sustainability of cementitious materials, binder system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Because numerous types of concrete with different admixtures are being created, the understanding of advanced concrete design procedures has expanded [ 4 ]. One of the outcomes of advanced concrete is self-compacting concrete, which was developed in Japan (1980) to produce high-strength and durable concrete structures [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because numerous types of concrete with different admixtures are being created, the understanding of advanced concrete design procedures has expanded [ 4 ]. One of the outcomes of advanced concrete is self-compacting concrete, which was developed in Japan (1980) to produce high-strength and durable concrete structures [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the modeling of early age creep, it is therefore recommended to integrate the degree of reaction in the model. Previous studies 49,50 have shown that the degree of hydration can be used as an aging parameter to model the basic creep of concrete composed of blended binders for which slag and fly ash correspond each to 20% of the cement mass. However, as early age basic creep relates to both hydrations of the Portland cement and slag, the impact of both materials on the specific creep function is divided into two distinct terms as expressed in Equation .…”
Section: Modelingmentioning
confidence: 99%
“…For the modelling of early age creep, it is therefore recommended to integrate the degree of reaction in the model. Previous studies (G. De Schutter et al, 2015;Jiang et al, 2014) have shown that the degree of hydration can be used as an aging parameter to model the basic creep of concrete composed of blended binders for which slag and fly ash correspond each to 20% of the cement mass.…”
mentioning
confidence: 99%
“…Temperature effects have been studied from the perspective of equivalent age [ 7 ], hydration degree [ 9 ], and transient creep [ 10 , 11 ], among others. Some calculation models, such as the B3 model [ 12 ], microprestress–solidification theory [ 13 ], rheological model [ 14 , 15 ], and degree of the hydration-based creep model [ 16 , 17 ] have been proposed to predict the effects of temperature on creep. Creep recovery is another important characteristic of creep.…”
Section: Introductionmentioning
confidence: 99%